PENERAPAN PRINSIP SYARIAH DALAM LEMBAGA PERASURANSIAN DI INDONESIA - Susamto, Burhanuddin (Fakultas Syariah, 2013)
TheÂ factÂ thatÂ theÂ insuranceÂ businessÂ institutionÂ hasÂ becomeÂ partÂ ofÂ Â IndonesianÂ people life. However, the question whether the practice of insurance is a legitimate according to Shariâ€™a law? To respond to these questions, DSN-MUI has issued some fatwas in order to practice the practice of insurance in accordance with Islamic principles to avoid gharar (uncertainty), gambling (gambling), riba (interest), zulmu (persecution), riswah (bribes), illicit goods, and immoral. Actually those fatwas had an impact so that the government was â€œforcedâ€ to adopt the principles of sharia into some regualasi insurance. This paper willÂ discussÂ theÂ regulatoryÂ aspectsÂ in Â additionÂ willÂ alsoÂ discussÂ howÂ theÂ applicationÂ of Shariâ€™a principles to the insurance agency. Kenyataan bahwa usaha perasuransian telah menjadi bagian dari kehidupan masyarakat diÂ Indonesia.Â NamunÂ yangÂ menjadiÂ pertanyaan,Â apakahÂ praktikÂ perasuransianÂ ituÂ sah hukumnya menurut tinjauan syariat? Untuk merespon pertanyaan tersebut, DSN-MUI telahÂ Â mengeluarkanÂ beberapaÂ fatwaÂ agarÂ praktikÂ perasuransianÂ sesuaiÂ denganÂ prinsipprinsipÂ syariah,Â Â sehinggaÂ terhindarÂ dariÂ Â ghararÂ (ketidakjelasan),Â maisirÂ (judi),Â riba (bunga), zulmu (penganiayaan), riswah (suap), barang haram, dan maksiat. Fatwa-fatwa tersebut ternyata telah memberikan pengaruh sehingga pemerintah â€terpaksaâ€ mengadopsi prinsip-prinsip syariah ke dalam beberapa regualasi perasuransian. Tulisan ini selain akan mengkajiÂ aspekÂ regulasiÂ perasuransian,Â jugaÂ mengkajiÂ bagaimanaÂ penerapanÂ prinsipprinsip syariah ke dalam lembaga tersebut.